Sacred Space and Multicultural Identity: A Study of Spatial Anthropology and Religious Studies at the Kong Fuk Miau Temple and Jamik Muntok Mosque in West Bangka - Jamil, Muhammad; Saprijal; Bariah, Chairul; Lasri; Hamda, Erna Fitriani (Biokultur, 2025)
This study discusses the existence of the Kong Fuk Miau Temple and the Jamik Muntok Mosque as two sacred spaces that stand side by side in the center of Muntok, West Bangka Regency. Chinese and Malay-Muslim communities since the 19th century. Using spatial anthropology and religious studies approaches, this research highlights how sacred spaces are produced, inhabited, and interpreted by different communities, while also serving as symbols of religious coexistence. The methods used include literature review, cultural heritage data analysis, and historical and ethnographic studies of ritual practices, spatial representations, and building materiality. The results of the analysis show that Kong Fuk Miau and Masjid Jamik not only function as centers of worship, but also as symbolic spaces of the city that represent tolerance, harmony, and cultural diversity. Spatially, the proximity of the two forms a threshold zone that facilitates social interaction and presents a distinctive religious heterotopia. Historically, the involvement of the Chinese and Malay communities in the development and maintenance of the site demonstrates a pattern of cross-ethnic collaboration that strengthens the collective identity of the city. This study confirms that the production of sacred space is not only related to architectural and ritual aspects, but also to public discourse, preservation policies, and the daily practices of the community. This study is expected to contribute to the development of spatial anthropology theory and religious studies in Indonesia, as well as strengthen understanding of the role of sacred spaces as a basis for tolerance and social integration in a multi-ethnic society.